Definitive‐intent intensity modulated radiotherapy for modified‐Adams' stage 4 canine sinonasal cancer: A retrospective study of 29 cases (2011‐2017). Issue 6 (26th July 2020) - Stevens, Audrey; Turek, Michelle; Vail, David; Christensen, Neil; Forrest, Lisa
Abstract: Dogs with sinonasal tumors with cribriform plate lysis (modified Adams' stage 4) treated with non‐conformal definitive radiotherapy (RT) have short median survivals of 6‐7 months. Intensity‐modulated radiotherapy with its greater conformality and tumor dose homogeneity may result in more favorable outcomes. Dogs with epithelial or mesenchymal sinonasal tumors and CT evidence of cribriform lysis that received 10 daily fractions of 4.2 Gray using IMRT by helical tomotherapy were included in this single‐institution retrospective case series study. Dogs with distant metastasis, previous treatment, or concurrent chemotherapy were excluded. Based on CT, tumors were divided into two groups: cribriform plate lysis only (stage 4a) or intracranial extension (stage 4b). Twenty‐nine dogs were included, 23 with carcinoma and six with sarcoma. Eight dogs had stage 4b tumors; two presented with neurologic signs. Two dogs had lymph node metastasis at diagnosis, one confirmed and one suspected. Radiation dose distributions were standardized and patient positioning for RT was verified daily using on‐board megavoltage CT. All evaluable dogs had improvement of clinical signs. Median progression free survival was 177 days (95% CI, 128‐294 days). Median overall survival was 319 days (95% CI, 188‐499 days). Radiotherapy was well tolerated. The most common side effect was grade 1 or 2 oral mucositis. Two dogs that received additional treatment at progression (stereotactic RT [1]; surgery [1]) developed significant late effects. Image‐guided definitive‐intent IMRT may improve survival in dogs with modified Adams' stage 4 sinonasal tumors and is associated with low morbidity. Intracranial tumor extension was not prognostic in this cohort of uniformly treated dogs.